Controlled Synthesis of PtNi Hexapods for Enhanced Oxygen Reduction Reaction - Song, Xing; Luo, Shuiping; Fan, Xiaokun; Tang, Min; Zhao, Xixia; Chen, Wen; Yang, Qi; Quan, Zewei (Frontiers in Chemistry, 2018)
Well-defined PtNi nanocrystals represent one of the most efficient electrocatalysts to boost the oxygen reduction reaction (ORR), especially in the shape of octahedrons, nanoframes and nanowires. However, the synthesis of complex PtNi nanostructure is still a great challenge. Herein, we report a new class of PtNi hexapods with high activity and stability towards ORR. The hexapods are prepared by selective capping and simultaneous corrosion. By controlling the oxidative etching, PtNi polyhedrons and nanoparticles are obtained, respectively. The intriguing hexapods are composed of six nanopods with an average length of 12.5 nm. Due to their sharp tips and three-dimensional (3D) accessible surfaces, the PtNi hexapods show a high mass activity of 0.85 A mgPt-1 at 0.9 V vs. RHE, which are 5.4-fold higher than commercial Pt/C, also outperforming PtNi polyhedrons and PtNi nanoparticles. In addition, the mass activity of PtNi hexapods maintains 92.3% even after 10000 potential cycles.